The Crucial Role of Domain Knowledge in Evaluating Early-Stage New Product Ideas - Denker, Florian (Forschungs-/Entwicklungs-/Innovations-Management, 2018)
Florian Denker explores the role of an individual's domain knowledge for the proficient evaluation of early-stage new product ideas in the front-end of innovation. The results of his study show that in order to ensure an effective evaluation, evaluators of early-stage new product ideas should have comprehensive knowledge of consumers' needs and wants, as well as distinct knowledge about the opportunities and limits of available technologies in the respective domain. In this context, the results show that not only firm-internal experts can have this knowledge. Users and, in particular, so-called "lead users" (i.e. users who are ahead of the majority on major market trends and innovations), could also be suitable for effectively evaluating early-stage new product ideas. Contents Front-end of innovation Foundations of research in the field of new idea evaluation Theoretical foundation of the role of individuals' domain knowledge in evaluating early-stage new product ideas Empirical study - new product idea evaluations by experts, users, and laymen Implications for research and practice Target Groups Researchers, lecturers and students of technology and innovation management, product development, and business management Practitioners and consultants in the field of innovation management, product development, and business development The Author Dr. Florian Denker graduated at the Institute of Technology and Innovation Management at the Hamburg University of Technology with Univ.-Prof. Dr. Cornelius Herstatt.